House Design Variables in Providing Indoor Thermal Comfort in Warm Humid Climate - Laina Hilma Sari; Zahriah (Journal of Architecture & Environment, 2020)
Housing design in warm-humid tropics is widely studied using various ways. In the climate, achieving low inside air temperature is challenged by high relative humidity for providing comfort. Therefore, this study aims at finding multiple ways in house design to achieve naturally indoor thermal comfort. In this case, house design variables were analyzed by using TAS (Thermal Analysis Software) building simulation software as well as supported by literature reviews. The simulations carried out some variables of dwelling design to identify the best approach to obtain low indoor thermal performance. In this study, the objective is to achieve the low inside air temperature by taking the weather data of Banda Aceh as the case study in TAS simulation. In this article, the house design variables discussed are building materials, shape, ventilation, house orientation, shading, and environmental indications.